Pengaruh Gaya Kepemimpinan Transformasional Terhadap Kinerja Karyawan yang Dimediasi oleh Motivasi Kerja pada Perusahaan CV. Cahaya Belawan Sejahtera, Samarinda, Kalimantan Timur - Nursabila, Aulia; Maria, Siti (Teewan Journal Solutions, 2026)
This study aims to analyze the effect of transformational leadership style on employee performance with work motivation as an intervening variable at CV. Cahaya Belawan Sejahtera, a coal mining company operating in Samarinda, East Kalimantan. The research employed a quantitative method with a survey approach. Data were collected through questionnaires distributed to all employees using saturated sampling technique, yielding 53 respondents. Data analysis was conducted using Partial Least Square (PLS) with SmartPLS 4.0 software. The results indicate that: (1) transformational leadership style has a positive and significant effect on employee performance (T-Statistic = 2.326; p = 0.020); (2) transformational leadership style has a positive and significant effect on work motivation (T-Statistic = 5.792; p = 0.000); (3) work motivation has a positive and significant effect on employee performance (T-Statistic = 5.635; p = 0.000); and (4) transformational leadership style has a positive and significant effect on employee performance through work motivation as a mediating variable (T-Statistic = 3.769; p = 0.000). The R-Square value for employee performance is 0.540, indicating that 54.0% of employee performance is explained by transformational leadership style and work motivation. This study confirms the importance of effective transformational leadership in enhancing employee motivation and performance in the mining sector.